DIURNAL VARIATION OF NUTRIENTS, WATER QUALITY AND PLANKTON COMPOSITION IN THE HAJAMRO CREEK (INDUS DELTA) DURING NORTH EAST MONSOON PERIOD - Saleem, M.; Aftab, J.; Kahkashan, S.; Kalhoro, N. A.; Ahmad, W. (The Nucleus, 2014)
Diurnal (24 hours) observations of dissolved nutrients, Chlorophyll-a, water quality (salinity, dissolved oxygen, temperature, pH and suspended solidmatter) were recorded at one site in the Hajamro Creek of Indus Delta during the North East Monsoon period. The zoo- and phyto-plankton were recorded during low and high tides. Primary productivity was measured only during the day time. Dissolved nutrient concentration ranges were NH4 (1.81 µM -12.30 µM), NO3 (0.03 µM -1.48 µM), NO2 (0.04 µM -0.122 µM), PO4 (0.45 µM -1.69 µM), SiO3 (4.84 µM -24.49 µM) and averages were 6.41, 0.28, 0.055, 0.722, 12.12 µM respectively. The suspended load ranged from 36.0 mg/l to 87.8 mg/l, pH from 8.24 to 8.38, temperature from 18.73 oC to 22.37 oC and salinity from 35.995 ppt - 37.062 ppt. Higher Chlorophyll-a concentration was recorded during the high tide in daytime and its range was 0.45 µg/l - 1.69 µg/l while its average concentration was 1.94 µg/l. The moderate value of primary productivity was recorded to be (0.475 g C/m3 /day). Eleven groups of zooplankton were identified. Copepods were the main species which were abundant during high tide. Bivalve, fish eggs, crab and polychaete larvae were observed during low tide. The present study shows that high amounts of suspended solids, dissolved nutrients (phosphate, silicate, nitrate and ammonia) and relatively more salinity in sea water were recorded during low tide. Presence of adequate dissolved nutrients and high turbidity is probably restricting productivity in the Hajamro Creek.